Dampak Pembuangan Sampah Terhadap Lingkungan di Pesisir Pantai Putra Deli - Kurnia Simbolon; Tamim Hasyimi; Dwidya Nuari; Meilinda Suriani Harefa; Syukri Hidayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Coastal environmental pollution is an increasingly complex problem in Indonesia, especially due to uncontrolled waste disposal. This study aims to analyze the impact of waste disposal on the environment in the coastal area of Putra Deli Beach, Deli Serdang Regency. The research approach used is mixed-method with data collection through direct observation, semi-structured interviews, and literature study. The results showed that plastic waste dominates the types of waste found at the research site and is the main cause of marine ecosystem pollution. The impacts include damage to marine biota habitat, decreased tourist attraction, public health problems, and economic losses for local businesses. The lack of waste management facilities and low environmental awareness also exacerbate this condition. Therefore, an integrated waste management strategy based on community and stakeholder collaboration is needed to maintain the sustainability of the coastal environment.